(untitled) (Research, Society and Development, 2022)
The word deafness is the correct term that corresponds to the impossibility or difficulty of hearing, that is, it makes it difficult for the individual to understand and communicate. According to research, deafness can be developed both by environmental and genetic factors, as well as the combination of environmental and genetic causes. In this sense, it is a fact that deaf people perceive the world around them differently from listeners, through a visual experience and the use of a specific language, such as Sign Language, which concerns the native language of deaf people. The general objective of this article is to discuss the psychological care of deaf people. This research was a narrative review, with a bibliographic procedure and a qualitative approach, using content analysis. The bibliographic research used articles, theses and books, obtained from the Pepsic, SciELO and Google Scholar databases. As a result of the research, it was observed that the deaf have great difficulties in relation to psychological care and communication emerges as a highlight in this scenario, since they are not attended in a qualified way, because in the current situation there is still a lack of trained psychologists to meet the demand in question.